Kontribusi Lingkungan Kerja, Kreativitas, dan Disiplin Terhadap Kinerja Tim dalam Industri Event Organizer - Candra, Orisa Ayu; Sutianingsih, Sutianingsih (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to analyze the influence of work environment, work creativity and work discipline on team performance at Royal W.O. The population of this study is the Royal W.O team which is 50 people. The sample of this study is 50 samples, with census sampling technique. This study is a quantitative research with multiple regression analysis techniques. From the results of hypothesis testing, there is a positive and significant influence between the work environment on team performance. Workplace innovation has a favorable and statistically significant effect on group output, according to the second hypothesis test. Results from the third hypothesis test showing that work discipline has a positive and statistically significant effect on team performance. From what we can tell from the tests, the determination coefficient is 0.858. In other words, the study model explains 86% of the variance in team performance factors due to differences in work environment, work inventiveness, and work discipline, while other variables account for the remaining 14%.